Drosophila as a Genetic Model for Hematopoiesis. Issue 2 (5th February 2019) - Banerjee, Utpal; Girard, Juliet R; Goins, Lauren M; Spratford, Carrie M
Abstract: In this FlyBook chapter, we present a survey of the current literature on the development of the hematopoietic system in Drosophila . The Drosophila blood system consists entirely of cells that function in innate immunity, tissue integrity, wound healing, and various forms of stress response, and are therefore functionally similar to myeloid cells in mammals. The primary cell types are specialized for phagocytic, melanization, and encapsulation functions. As in mammalian systems, multiple sites of hematopoiesis are evident in Drosophila and the mechanisms involved in this process employ many of the same molecular strategies that exemplify blood development in humans. Drosophila blood progenitors respond to internal and external stress by coopting developmental pathways that involve both local and systemic signals. An important goal of these Drosophila studies is to develop the tools and mechanisms critical to further our understanding of human hematopoiesis during homeostasis and dysfunction.